(4x+16)(3x-9)=12x-36x

Simple and best practice solution for (4x+16)(3x-9)=12x-36x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (4x+16)(3x-9)=12x-36x equation:


Simplifying
(4x + 16)(3x + -9) = 12x + -36x

Reorder the terms:
(16 + 4x)(3x + -9) = 12x + -36x

Reorder the terms:
(16 + 4x)(-9 + 3x) = 12x + -36x

Multiply (16 + 4x) * (-9 + 3x)
(16(-9 + 3x) + 4x * (-9 + 3x)) = 12x + -36x
((-9 * 16 + 3x * 16) + 4x * (-9 + 3x)) = 12x + -36x
((-144 + 48x) + 4x * (-9 + 3x)) = 12x + -36x
(-144 + 48x + (-9 * 4x + 3x * 4x)) = 12x + -36x
(-144 + 48x + (-36x + 12x2)) = 12x + -36x

Combine like terms: 48x + -36x = 12x
(-144 + 12x + 12x2) = 12x + -36x

Combine like terms: 12x + -36x = -24x
-144 + 12x + 12x2 = -24x

Solving
-144 + 12x + 12x2 = -24x

Solving for variable 'x'.

Reorder the terms:
-144 + 12x + 24x + 12x2 = -24x + 24x

Combine like terms: 12x + 24x = 36x
-144 + 36x + 12x2 = -24x + 24x

Combine like terms: -24x + 24x = 0
-144 + 36x + 12x2 = 0

Factor out the Greatest Common Factor (GCF), '12'.
12(-12 + 3x + x2) = 0

Ignore the factor 12.

Subproblem 1

Set the factor '(-12 + 3x + x2)' equal to zero and attempt to solve: Simplifying -12 + 3x + x2 = 0 Solving -12 + 3x + x2 = 0 Begin completing the square. Move the constant term to the right: Add '12' to each side of the equation. -12 + 3x + 12 + x2 = 0 + 12 Reorder the terms: -12 + 12 + 3x + x2 = 0 + 12 Combine like terms: -12 + 12 = 0 0 + 3x + x2 = 0 + 12 3x + x2 = 0 + 12 Combine like terms: 0 + 12 = 12 3x + x2 = 12 The x term is 3x. Take half its coefficient (1.5). Square it (2.25) and add it to both sides. Add '2.25' to each side of the equation. 3x + 2.25 + x2 = 12 + 2.25 Reorder the terms: 2.25 + 3x + x2 = 12 + 2.25 Combine like terms: 12 + 2.25 = 14.25 2.25 + 3x + x2 = 14.25 Factor a perfect square on the left side: (x + 1.5)(x + 1.5) = 14.25 Calculate the square root of the right side: 3.774917218 Break this problem into two subproblems by setting (x + 1.5) equal to 3.774917218 and -3.774917218.

Subproblem 1

x + 1.5 = 3.774917218 Simplifying x + 1.5 = 3.774917218 Reorder the terms: 1.5 + x = 3.774917218 Solving 1.5 + x = 3.774917218 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1.5' to each side of the equation. 1.5 + -1.5 + x = 3.774917218 + -1.5 Combine like terms: 1.5 + -1.5 = 0.0 0.0 + x = 3.774917218 + -1.5 x = 3.774917218 + -1.5 Combine like terms: 3.774917218 + -1.5 = 2.274917218 x = 2.274917218 Simplifying x = 2.274917218

Subproblem 2

x + 1.5 = -3.774917218 Simplifying x + 1.5 = -3.774917218 Reorder the terms: 1.5 + x = -3.774917218 Solving 1.5 + x = -3.774917218 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1.5' to each side of the equation. 1.5 + -1.5 + x = -3.774917218 + -1.5 Combine like terms: 1.5 + -1.5 = 0.0 0.0 + x = -3.774917218 + -1.5 x = -3.774917218 + -1.5 Combine like terms: -3.774917218 + -1.5 = -5.274917218 x = -5.274917218 Simplifying x = -5.274917218

Solution

The solution to the problem is based on the solutions from the subproblems. x = {2.274917218, -5.274917218}

Solution

x = {2.274917218, -5.274917218}

See similar equations:

| (2x-5)(3x-50)=180 | | 4t-t= | | y^2+4y-72=180 | | 50x+4=7x+35 | | 0=k-9 | | y-11=1 | | -108=-3+7(7b-8) | | 4+y=15 | | 12x-5-8x+5=x-8x+5 | | 4x+10+10=180 | | 8y-(-5y-15)=13 | | y-15=-10 | | x^2+11x=4x+49 | | y+7y=40 | | 8h+3=75 | | -5n(4-3n)=10(n-2) | | 2x+2(4x)+38=180 | | 7-2n=8n(4n) | | 0.875p=-3.75 | | 7y-3x+8=0 | | 0.06666666666666666666666666666667-0.1666666666666667v=0.5333333333333333 | | x^2+7x=26 | | 10m-20=80 | | 5n+10= | | 14-y=0 | | 4x-3x=-6+8 | | 1+y=16 | | 3h+2=5h-15 | | -7j+-4j= | | y-0.4y= | | 5a/6-4=1 | | 4x+-6x+2x= |

Equations solver categories